Existential phenomenology as a unifying philosophy of science for a mixed method study - Pedersen, Birgith (Nursing philosophy, 2022)
This article discusses how existential phenomenology may serve as a frame in a mixed-methods study of changes in weight and body composition among women in adjuvant treatment for breast cancer. In accordance with ontologically and epistemologically fundamental assumptions in nursing, we link mixed-methods and existential phenomenology from the perspective of the French philosopher Maurice Merleau-Ponty and his notion of a unified body subject. Letting this perspective permeate our philosophy, methodology and issues at the method level in mixed-method research undermines the distinction between first- and third-person perspective when applying and integrating different data sources in a mixed-methods study. Applying Merleau-Ponty's third way, the women's bodily experiences appear as gestalt; a ‘figure’ against a ground of existential threats that are grasped through insight from data integrating in joint displays, which revealed the women's experiences on a deep existential level. Existential phenomenology as a frame in mixed-method studies can speak not only to nurses but also to a multidisciplinary audience in a shared attempt to deepen the understanding of a patient's healthcare problem.